Pertumbuhan Kembang Balita di Posyandu Bunga Matahari RW 08 Kelurahan Labuh Baru Timur Pekanbaru - Abdul Kudus Zaini; Cyintia Kumalasari; Muhammad Zainal Muttaqin (Pusat Riset dan Inovasi Nasional, 2023)
Monitoring growth and development is an activity to detect early deviations in growth (deficient or poor nutritional status, short children), developmental deviations (delayed speaking), and mental and emotional deviations in children (impaired concentration and hyperactivity). The aim of this community service is to increase public knowledge about the normal growth and development of toddlers and increase mothers' awareness about the importance of stimulating toddler growth and development. A survey conducted by the Community Service Team on mothers with toddlers stated that posyandu officers at the East Labu Baru Health Center lacked education, especially regarding the growth and development of toddlers. The method of implementing this service was through midwife and doctor discussions, questions and answers, and weight checks on toddlers. The service was carried out at Posyandu Bunga Matahari, RW 08 Labuh Baru Timur Village. Under the target of every mother who has a toddler, it will be held every month on September 13, 2023. After the outreach activities are carried out, the participants who attend understand how to monitor the growth and development of toddlers and can monitor the ideal body weight of toddlers.